Implementation and Evaluation of Resuscitation Training for Childcare Workers - Michel, Jörg; Ilg, Tim; Neunhoeffer, Felix; Hofbeck, Michael; Heimberg, Ellen (Frontiers in Pediatrics, 2022)
Background and Objective: Children spend a large amount of time in daycare centers or schools. Therefore, it makes sense to train caregivers well in first-aid measures in children. The aim of this study is to evaluate whether a multimodal resuscitation training for childcare workers can teach adherence to resuscitation guidelines in a sustainable way. Material and Methods: Caregivers at a daycare center who had previously completed a first-aid course received a newly developed multimodal resuscitation training in small groups of 7-8 participants by 3 AHA certified PALS instructors and providers. The 4-hour focused retraining consisted of a theoretical component, expert modeling, resuscitation exercises on pediatric manikins (Laerdal Resusci Baby QCPR), and simulated emergency scenarios. Adherence to resuscitation guidelines was compared before retraining, immediately after training, and after 6 months. This included evaluation of chest compressions per round, chest compression rate, compression depth, full chest recoil, no-flow time, and success of rescue breaths. For better comparability and interpretation of the results, the parameters were evaluated both separately and summarized in a resuscitation score reflecting the overall adherence to the guidelines. Results: A total of 101 simulated cardiopulmonary resuscitations were evaluated in 39 participants. In comparison to pre-retraining, chest compressions per round (15.0 [10.0-29.0] vs. 30.0 [30.0-30.0], p<0.001), chest compression rate (100.0 [75.0-120.0] vs. 112.5 [105.-120.0], p<0.001), correct compression depth (6.7% [0.0- 100.0] vs. 100.0% [100.0- 100.0], p<0.001), no-flow time (7.0sec. [5.0-9.0] vs. 4.0sec. [3.0-5.0], p<0.001), success of rescue breaths (0.0% [0.0-0.0] vs. 100.0% [100.0-100.0], p<0.001), and resuscitation score were significantly improved immediately after training (3.9 [3.2-4.9] vs. 6.3 [5.6-6.7], p<0.001). At follow-up, there was no significant change in chest compression rate and success of rescue breaths. Chest compressions per round (30.0 [15.0-30.0], p<0.001), no-flow time (5.0sec. [4.0-8.0], p<0.001), compression depths (100.0% [96.7-100.0], p<0.001), and resuscitation score worsened again after 6 months (5.7 [4.7-6.4], p=0.03). However, the results were still significantly better compared to pre-retraining. Conclusions: Our multimodal cardiopulmonary resuscitation training program for caregivers is effective to increase the resuscitation performance immediately after training. Although the effect diminishes after 6 months, adherence to resuscitation guidelines was significantly better than before retraining.